Hubungan Antara Minat Belajar dan Prestasi Belajar Siswa pada Mata Pelajaran Seni Budaya (Studi Korelasi pada Siswa Kelas VIII SMP N 2 Arga Makmur - Wijayanto, Nasib Suprapto (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2015)
The purpose of this research is for investigating whether or not there is a relationship between learning interest and learning achievement in the subject of art and culture for the eighth class students in SMP Negeri 2 Arga Makmur.The method used in this research isquantitative research, especially correlationresearch design. The subject of this research is the eighthclass students of SMPN 2 Arga Makmur in the academic year 2014/2015. The instument used in this research is a questionnaire about learning interest and a test for the subject of art and culture. The results of the research are analyzed by correlation analysis using Product Moment (Pearson) formula. From the result of the calculation, it is found that rcount is 0,758. It is higher than rtable (0,758 >0,423), thus, the alternative hypothesis (Ha) is accepted and the null hypohesis (H0) is rejected. It indicates that there is a significant correlation between the variables.The value of r count is positive, it means that there is a positive correlation between the variables. As the result, it was concluded that there is a strongly significant and positive correlation betweenlearning interest and learning achievement in the subject of Seni Budayafor the eighth class students in SMP Negeri 2 Arga Makmur.